Moving from pediatric to adolescent HIV care in Northern Tanzania: exploring transition services, perceptions and self-care during early adolescence - Lisasi, Esther (Department of Public Health and Family Medicine, 2025)
Given the increased survival of children with perinatally acquired HIV into adolescence due to increased coverage and access to antiretroviral therapy (ART) for children in Sub Saharan Africa (SSA), the pediatric-to-adolescent transition in HIV care is now of public health importance. There is, however, limited information available regarding pediatric-to-adolescent transition practices and how best to transition adolescents with perinatally acquired HIV from pediatric to adolescent HIV care clinics in Tanzania. This study therefore sought to understand how best to move adolescents with perinatally acquired HIV from pediatric to adolescent HIV care in Northern Tanzania during early adolescence. The specific objectives were: 1. To understand the current organization of pediatric-to-adolescent transitional care services and how this organization affects the perceptions and attitudes of transitioning adolescents during early adolescence. 2. To explore contextual factors other than service delivery that affect adolescents' and their caregivers' perceptions and attitudes towards transition before and after the move to adolescent clinics. 3. To understand the immediate effects of the transition from pediatric to adolescent care on medication adherence and clinic attendance management during early adolescence. Methods This was a mixed methods study that was carried out in three phases at two adolescent clinics in Northern Tanzania (KCMC zonal referral hospital and Mawenzi regional hospital). The first phase of the study was quantitative and used routinely collected clinical data of 345 adolescents aged ten to 18 years who were receiving HIV care in both hospitals. The second phase was a qualitative exploratory study that used in-depth interviews (IDIs) with eight adolescents who had already moved from pediatric to adolescent clinic. The third phase was a one-year longitudinal qualitative study that included repeated IDIs and focus group discussions with eight adolescents who were about to transition to adolescent clinics, eight of the adolescents' caregivers and ten service providers. Results Findings from the quantitative study show that there was no difference in socio-demographic and clinical characteristics of adolescents between the two hospitals and between transitioned and untransitioned adolescents. However, viral load suppression remained a challenge in many adolescents, regardless of whether they had transitioned to adolescent clinic or not. Despite three years of transitioning adolescents from pediatric to adolescent clinic, a huge backlog persisted, xi with 46% of eligible adolescents in the 13-18-year age group still receiving care in pediatric clinic at both hospitals indicating a service gap in the transition process. Exploration of the organization of pediatric-to-adolescent transition using qualitative methods revealed that disclosure of adolescents' HIV status was the essential factor to the pediatric-to adolescent transition. All adolescents had to be aware of their HIV status prior moving to the adolescent clinics. Medication adherence, virologic assessment, type of regimen, psychosocial maturity and mental health were also identified as critical aspects of readiness assessment prior to moving to adolescent clinic. High levels of caregiver engagement, interaction, communication, and support were required to guide the transition, particularly for caregivers living with HIV who have been receiving HIV care together with their adolescents since childhood. Overall, there was a well-established transition practice. However, the lack of written protocols/national guidelines and the limited availability of human resources were the limiting factors to the provision of evidence-informed transition practices. Hence, variations in pediatric-to-adolescent transition practices across healthcare facilities in Tanzania are likely to occur given the absence of national guidelines governing this process. Exploration of influential factors revealed that psychosocial adjustment following disclosure, perceived self-efficacy, perceived stigma as well as feelings of personal responsibility, privacy and confidentiality at the clinic were all individual level factors that affected acceptability of the adolescent clinic and adolescents' continuation with care after transition At caregiver level, caregiver readiness and especially caregivers living with HIV who are also required to transition to adult clinic, fear of stigma and critical events in the family influenced caregivers' decisions regarding the pediatric-to-adolescent transition. At all stages of the transition to adolescent clinic, peer influence and support were important factors. The organization of transition services also affected adolescents' decisions and care continuity, especially in health facility settings where moving to a different clinic could lead to HIV identification. Transition practices requiring adolescents to move to an adult clinic in the event of pregnancy or marriage before age 24 limited pediatric-to-adolescent transition success. Finally, broader structural factors such as the education system where adolescents in grade seven are required to attend classes on Saturdays and the religion where most adolescents attend religious (confirmation and madrassa) classes on Saturdays also influenced adolescents' and caregivers' perceptions towards this transition. Lastly, since many adolescents in Tanzania attend boarding schools, these impacted not only the pediatric-to-adolescent transition process but also continuity with HIV care due to a lack of HIV services in boarding schools and lack of privacy in keeping and taking of one's medicines. xii Immediate effects of the pediatric-to-adolescent transition on the level of responsibilities assumed by adolescents were mixed. In some adolescents, the pediatric-to-adolescent transition resulted in an increase in medication adherence and clinic attendance responsibilities, whereas in others, medication adherence and clinic attendance responsibilities decreased or were unaffected. Several factors contributed to these outcomes which include peer influence, peer support, sense of responsibility for one's health, the level of caregivers' engagement in these activities, adolescents' living conditions and fear of stigma. Adolescents appeared to often assume responsibilities for medication adherence and clinic attendance well before the transition period and adolescents of caregivers living with HIV assumed more responsibilities than other adolescents. However, there was no national transition guide to assist healthcare workers in providing systematic and evidence-based support to caregivers in transferring autonomy to adolescents for clinic attendance and medication adherence related tasks. As a result, it may be challenging to ensure smooth transition of responsibilities from caregivers to adolescents in a chronologically, developmentally, behaviorally, clinically, psychologically and culturally appropriate manner for the Tanzanian context. Conclusion In conclusion, the pediatric-to-adolescent transition of HIV care for adolescents living with perinatally acquired HIV is a bi-faceted (adolescent and caregivers), multi-stage (from disclosure to transition to adult clinic) and ongoing process that needs to attend to the medical, psychosocial, and developmental needs of adolescents at all stages as well as caregivers' needs. This pediatric to-adolescent transition provides a chance to strengthen adolescents' autonomy and connections to their peers and friends which is an important psychosocial aspect of HIV care and highly valued by adolescents. Therefore, with adequate planning, oversight, and adolescent and caregiver involvement in all transition stages, pediatric-to-adolescent transitional programs can increase adolescents' engagement in care, lead to timely identification of risk factors influencing this transition, and eventually foster self-care to transitioning adolescents.